Activity of the herbicide acetochlor in soil under no-till and conventional tillage systems - Ferri, Miguel Vicente Weiss; Vidal, Ribas Antonio; Gomes, Juliana; Dick, Deborah Pinheiro; de Souza, Roberto Fernando (Pesquisa Agropecuaria Brasileira, 2002)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The activity of herbicide acetochlor in a Red Argisol (Paleudult) under no-till and conventional tillage systems was investigated in laboratory and field experiments. The herbicide was less efficient on weed control under no-till system than under conventional tillage. The reduction of wheat dry matter, evaluated in the sample collected from the 16-19 cm depth, was higher under no-till, suggesting a greater leaching capacity in this soil tillage system. The acetochlor sorption was higher on no-till system than in the conventional tillage, as indicated by the distribution coefficients on soil (Kd): 2.75 and 1.67 L kg-1, respectively. The distribution coefficients relative to the soil organic carbon (Koc) were 166 L kg-1 on no-till and 126 L kg-1 on conventional tillage, showing that the herbicide was sorbed in a greater extent by the organic matter from the no-till system.